Mechanisms and Treatment of Blast Induced Hearing Loss - Choi, Chul-Hee (The Korean Audiological Society, 2012)
The main objective of this study is to provide an overview of the basic mechanisms of blast induced hearing loss and review pharmacological treatments or interventions that can reduce or inhibit blast induced hearing loss. The mechanisms of blast induced hearing loss have been studied in experimental animal models mimicking features of damage or injury seen in human. Blast induced hearing loss is characterized by perforation and rupture of the tympanic membrane, ossicular damage, basilar membrane damage, inner and outer hair cell loss, rupture of round window, changes in chemical components of cochlear fluid, vasospasm, ischemia, oxidative stress, excitotoxicity, hematoma, and hemorrhage in both animals and humans. These histopathological consequences of blast exposure can induce hearing loss, tinnitus, dizziness, and headache. The pharmacological approaches to block or inhibit some of the auditory pathological consequences caused by blast exposure have been developed with antioxidant drugs such as 2,4-disulfonyl α-phenyl tertiary butyl nitrone (HXY-059, now called HPN-07) and N-acetylcysteine (NAC). A combination of antioxidant drugs (HPN-07 and NAC) was administered to reduce blast induced cochlear damage and hearing loss. The combination of the antioxidant drugs can prevent or treat blast induced hearing loss by reducing damage to the mechanical and neural component of the auditory system. Although information of the underlying mechanisms and treatment of blast induced hearing loss are provided, further and deep research should be achieved due to the limited and controversial knowledge.